Wspieranie działalności małych i średnich przedsiębiorstw w Niemczech - Sojkin, Bogdan; Urbanowska-Sojkin, Elżbieta (My University, 1991)
The article presents basic issues of functioning of small and medium enterprises in Germany. Special attention is paid to crediting and consulting. The authors discuss levels and forms of credit offered to small and medium companies and present institutions that implement various credit programmes. The authors also discuss the issues connected with consulting as well as with research and development programmes. All issues are illustrated with recent statistical data.
Te ways of supporting the activity of small and medium enterprises in Germany